Estereoquímica y configuración absoluta de diterpenos del género Caesalpinia - Álvarez Esquivel, Fany Elisa (Universidad Michoacana de San Nicolás de Hidalgo, 2012)
The chromatographic separation of the methylene chloride extract from the leaves of C. platyloba allowed the isolation of natural product 1, which is a new compound and was characterized by 13C and 1H NMR spectroscopy, its absolute configuration was determined by Dichroism Vibrational Circular, X-ray diffraction and chemical correlation. From 6β-acetoxivoucapane (1) derivatives 3 and 4 were obtained, were characterized by their spectroscopic data and their absolute configuration was established by DCV. The genus Caesalpinia is a rich source of diterpenfuran type cassians and there are several reports on its biological properties such as antimalaria, antiviral and anticancer among others. Pamatz et al. For the first time, they isolated 1 of C. platyloba and C. coriaria and measured their cytotoxic activity but did not establish their absolute configuration, so in this work their molecular structure was established unequivocally by the methods already mentioned. For the DCV calculations a conformational study was carried out in Spartan´10 using molecular mechanics, then it was optimized with Gaussian´03 using functional theory of DFT density with B3LYP631G ** and DGDZVP. The experimental and theoretical DCV spectra had a good level of similarity, so the absolute configuration of (5S, 6R, 8S, 9S, 10R, 14R) -6- acetoxivoucapane (1), (5S, 6R, 8S, 9S was established , 10R, 14R) -6-hydroxivoucapane (3) and (5S, 8S, 9S, 10R, 14R) -6-oxovoucapane (4).

La separación cromatográfica del extracto de cloruro de metileno de las hojas de C. platyloba permitió el aislamiento del producto natural 1, el cuál es un nuevo compuesto y fue caracterizado por espectroscopia de RMN de 13C y de 1H, su configuración absoluta se determinó por Dicroísmo Circular Vibracional, difracción de rayos X y correlación química. A partir del 6β-acetoxivoucapano (1) se obtuvieron los derivados 3 y 4, fueron caracterizados por sus datos espectroscópicos y su configuración absoluta se estableció por DCV. El género Caesalpinia es una fuente rica en cassanos tipo diterpenfuranos y existen varios reportes sobre sus propiedades biológicas como antimalaria, antiviral y anticancerígenos entre otras. Pamatz y col. aislaron por primera vez 1 de C. platyloba y C. coriaria y midieron su actividad citotóxica pero no establecieron su configuración absoluta, por lo que en el presente trabajo se estableció su estructura molecular inequívoca por los métodos ya mencionados. Para los cálculos de DCV se llevó a cabo un estudio conformacional en Spartan´10 usando mecánica molecular, después se optimizó con Gaussian´03 usando teoría de funcionales de la densidad DFT con B3LYP631G** y DGDZVP. Los espectros de DCV experimental y teórico tuvieron buen nivel de similitud por lo que se estableció la configuración absoluta del (5S, 6R, 8S, 9S, 10R, 14R)-6- acetoxivoucapano (1), (5S, 6R, 8S, 9S, 10R, 14R)-6-hidroxivoucapano (3) y (5S, 8S, 9S, 10R, 14R)-6-oxovoucapano (4).
Instituto de Investigaciones Químico Biológicas. Maestría en Ciencias Químicas
Keywords: info:eu-repo/classification/cti/2; IIQB-M-2012-0010; Cloruro de metileno; Dicroísmo circular vibracional; Rayos X; Correlación química; DCV; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/2261